Method for preparing ceramic-based composite material by PIP improved process
By introducing pretreatment, low-temperature pre-cracking, high-temperature cracking and high-temperature ceramicization steps in the PIP process, the problems of high porosity and low mechanical properties of C/SiC composite materials in the existing PIP process are solved, and ceramic matrix composite materials with higher density and more uniform ceramic phase distribution are achieved.
Patent Information
- Application Number
- CN202510088178.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The C/SiC composite materials prepared by the existing PIP process have high internal porosity, low mechanical properties, and insufficient oxidation resistance for a long time.
A PIP improvement process is adopted, including pretreatment materials, polymer impregnation, low-temperature pre-cracking, high-temperature cracking and high-temperature ceramicization steps, through which a high density and uniform ceramic phase distribution is formed.
It significantly reduces the porosity of the composite material, improves the mechanical properties and oxidation resistance, and improves the quality and density of the ceramic matrix.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic-based composite materials, in particular to a method for preparing ceramic-based composite materials through a PIP improved process. Background Art
[0002] Ceramic matrix composites have the characteristics of low density, high temperature resistance, high hardness, oxidation resistance, and excellent mechanical properties. As high-temperature thermal structural materials, they are widely used in the aerospace field. At present, the molding process methods of ceramic matrix composites include chemical vapor infiltration (CVI), precursor conversion (PIP) and reactive melt infiltration (RMI).
[0003] The PIP process has the advantages of large impregnation depth and small product density gradient. However, since a large number of small molecules of polycarbosilane used in the PIP process overflow during the cracking process, the cracking product is in an expanded foaming state with a large number of holes inside. Even after multiple PIP process steps, the holes cannot be completely filled. As a result, the C / SiC composite material prepared by the PIP process has a high internal porosity (>12%), low mechanical properties, and insufficient long-term antioxidant capacity.
[0004] The method to improve the performance of C / SiC composites prepared by PIP process generally adopts CVI and PIP composite process, that is, CVI process is used in the early stage to realize the matrix densification of micropores in fiber bundles, and PIP process is used in the later stage to realize the matrix densification of macropores between fiber bundles, which can give full play to the advantages of CVI process and PIP process, but there are still a large number of holes in the C / SiC composites prepared by this composite process, and the porosity is generally >10%. In order to further reduce the porosity of C / SiC composites, low molecular weight polycarbosilane is used for PIP process at the end of the composite process, and the porosity is reduced to a certain extent, but the effect is not obvious.
[0005] In view of the above problems, it is very necessary to provide a method for preparing ceramic-based composite materials by an improved PIP process and a ceramic-based composite material with excellent comprehensive performance obtained thereby. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a ceramic matrix composite material by an improved PIP process to solve the above problems.
[0007] To achieve the above object, the present invention provides a method for preparing a ceramic matrix composite material by an improved PIP process, comprising the following steps:
[0008] 1) Pre-treat the material, select appropriate reinforcement material and matrix material, process the reinforcement material into the desired shape, and form the reinforcement material into a three-dimensional network structure through weaving, lamination or other molding processes;
[0009] 2) Polymer infiltration: placing the reinforcement material in a liquid polymer, and using vacuum infiltration, pressure infiltration or room temperature infiltration, the polymer is infiltrated into the voids of the reinforcement material to fill its internal structure and form a polymer matrix;
[0010] 3) Pre-cracking of the polymer matrix at low temperature: the polymer matrix after infiltration is first pre-cracking at low temperature, and the reinforcing material infiltrated with the polymer is heated;
[0011] 4) High temperature cracking of the polymer matrix. To increase the density of the composite material and improve the quality of the ceramic matrix, repeated heating and cracking processes are performed to fill the original gaps;
[0012] 5) High temperature ceramicization of the polymer matrix promotes the formation of ceramic reinforcement phase and makes the ceramic phase distribution more uniform.
[0013] Preferably, in the above method for preparing a ceramic-based composite material by an improved PIP process, the reinforcing material in step 1) is carbon fiber or silicon fiber.
[0014] Preferably, in the above method for preparing ceramic-based composite materials by using an improved PIP process, the liquid polymer in step 2) includes polyvinyl alcohol, epoxy resin, or phenolic resin.
[0015] Preferably, in the above method for preparing ceramic-based composite materials by an improved PIP process, the temperature of the low-temperature pre-cracking in step 3) is 400-600° C., and the cracking time is 1-4 hours.
[0016] Preferably, in the above method for preparing ceramic-based composite materials by an improved PIP process, the temperature of the high-temperature pyrolysis in step 4) is 1400-1600° C., and the pyrolysis time is 2-6 hours.
[0017] Preferably, in the above method for preparing a ceramic-based composite material by an improved PIP process, the temperature of high-temperature ceramicization in step 5) is 1600-1800° C., and the pyrolysis time is 1-2 h.
[0018] Therefore, the method for preparing a ceramic-based composite material by using a PIP improved process of the above structure in the present invention has the following beneficial effects:
[0019] The low-temperature pre-cracking process reduces the preparation cycle, improves the impregnation efficiency, and requires simple equipment, low maintenance costs, and can be mass-produced. In addition, the low-temperature pre-cracking process greatly reduces the damage to the carbon fiber matrix and improves the mechanical properties of ceramic-based composites.
[0020] The process of combining high-temperature pyrolysis and high-temperature ceramicization can not only meet the requirements of impregnation and formation of ceramic reinforcement phase, but also reduce the damage of high temperature to the carbon fiber matrix to a certain extent.
[0021] The PIP process is optimized by using one low temperature and two high temperatures. The prepared composite material has low porosity and uniform ceramic phase distribution. Compared with the mechanical properties of the conventional process, the ceramic-based composite material prepared by the improved process has better mechanical properties, and its ablation performance has not decreased significantly, providing a more efficient process for the production of high-temperature thermal structure components and complex components in the aerospace industry.
[0022] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0023] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0025] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0026] The present application provides a method for preparing a ceramic matrix composite material by an improved PIP process, comprising the following steps:
[0027] 1) Pre-treat the material, select appropriate reinforcement material and matrix material, process the reinforcement material into the desired shape, and form the reinforcement material into a three-dimensional network structure through weaving, lamination or other molding processes;
[0028] 2) Polymer infiltration: placing the reinforcement material in a liquid polymer, and using vacuum infiltration, pressure infiltration or room temperature infiltration, the polymer is infiltrated into the voids of the reinforcement material to fill its internal structure and form a polymer matrix;
[0029] 3) Pre-cracking of the polymer matrix at low temperature: the polymer matrix after infiltration is first pre-cracking at low temperature, and the reinforcing material infiltrated with the polymer is heated;
[0030] 4) High temperature cracking of the polymer matrix. To increase the density of the composite material and improve the quality of the ceramic matrix, repeated heating and cracking processes are performed to fill the original gaps;
[0031] 5) High temperature ceramicization of the polymer matrix promotes the formation of ceramic reinforcement phase and makes the ceramic phase distribution more uniform.
[0032] In step 1), the reinforcing material is carbon fiber or silicon fiber.
[0033] In step 2), the liquid polymer includes polyvinyl alcohol, epoxy resin, and phenolic resin.
[0034] In step 3), the temperature of low-temperature pre-cracking is 400-600° C., and the cracking time is 1-4 hours.
[0035] In step 4), the temperature of high temperature cracking is 1400-1600° C., and the cracking time is 2-6 hours.
[0036] In step 5), the temperature of high temperature ceramicization is 1600-1800° C., and the cracking time is 1-2 hours.
[0037] Example 1
[0038] Carbon fiber reinforced ceramic matrix composite material, the reinforcing material is carbon fiber, and the carbon fiber is woven into a three-dimensional network structure by a weaving process.
[0039] Epoxy resin is selected as the liquid polymer, and the epoxy resin is impregnated into the gaps in the carbon fiber three-dimensional network structure by vacuum infiltration.
[0040] The impregnated polymer matrix was pre-cracked at low temperature, with the temperature set at 400°C and the cracking time being 2 hours.
[0041] The high temperature cracking treatment was carried out, the temperature was set to 1400°C, and the cracking time was 4 hours.
[0042] Finally, high temperature ceramicization is carried out at a temperature of 1600°C and a ceramicization time of 1 hour.
[0043] The carbon fiber reinforced ceramic matrix composite material prepared by this method has good high temperature stability, wear resistance and strong mechanical properties. The high temperature pyrolysis and ceramicization process helps to increase the density of the composite material, reduce the voids, and significantly improve the quality of the ceramic matrix, so that it exhibits excellent thermal stability and thermal shock resistance in high temperature environments.
[0044] Example 2
[0045] Silicon fiber reinforced ceramic matrix composite material, the reinforcing material is selected from silicon fiber, and the silicon fiber is stacked into a multi-layer structure by a lamination process.
[0046] Polyvinyl alcohol is selected as the liquid polymer, and the polyvinyl alcohol is fully infiltrated into the gaps between the silicon fiber layers by pressure infiltration.
[0047] The impregnated polymer matrix was pre-cracked at low temperature, with the temperature set at 500°C and the cracking time being 3 hours.
[0048] The high temperature cracking treatment was carried out, the temperature was set to 1500°C, and the cracking time was 5 hours.
[0049] Finally, high temperature ceramicization is carried out at a temperature of 1700°C and a ceramicization time of 1.5 hours.
[0050] The prepared silicon fiber reinforced ceramic matrix composite material has high strength and toughness, and excellent high temperature oxidation resistance. Through reasonable infiltration, cracking and ceramicization process, the combination of silicon fiber and ceramic matrix is enhanced, the porosity is reduced, and the overall mechanical properties and thermal stability of the material are improved, especially the durability in high temperature environment is significantly improved.
[0051] Example 3
[0052] The hybrid fiber (carbon fiber and silicon fiber) reinforced ceramic matrix composite material uses a hybrid material of carbon fiber and silicon fiber, and adopts a combination of weaving and lamination to form a three-dimensional network structure with double reinforcement effects.
[0053] The liquid polymer is phenolic resin, which is infiltrated into the gaps of the mixed fibers by a room temperature infiltration method to form a uniform polymer matrix.
[0054] The impregnated polymer matrix was pre-cracked at low temperature, with the temperature set at 600°C and the cracking time being 4 hours.
[0055] The high temperature cracking treatment was carried out, the temperature was set to 1650°C, and the cracking time was 6 hours.
[0056] Finally, high temperature ceramicization is carried out at a temperature of 1800°C and a ceramicization time of 1 hour.
[0057] Ceramic matrix composites reinforced with hybrid fibers can give full play to the excellent properties of carbon fibers and silicon fibers, providing a dual reinforcement effect. Through the PIP improvement process, the composite material has low porosity, uniform distribution of the reinforcement phase, and greatly improved comprehensive mechanical properties, high temperature resistance, and thermal shock resistance. This material has broad application prospects in environments requiring high strength and high temperature resistance, such as aerospace, thermal protection and other fields.
[0058] Examples 1-3 can effectively improve the density, mechanical properties and high temperature stability of ceramic matrix composites by using different types of reinforcing materials (carbon fiber, silicon fiber and their mixed materials) and different liquid polymers (epoxy resin, polyvinyl alcohol, phenolic resin) and different heat treatment processes. Finally, through the high temperature ceramicization process, not only can the performance of the composite material be significantly improved, but also the uniform distribution of the ceramic reinforcement phase can be ensured, thereby meeting the performance requirements of the composite material in different application fields.
[0059] Therefore, the present invention adopts a method for preparing ceramic-based composite materials using a PIP improved process of the above structure, adopts a low-temperature pre-cracking process, reduces the preparation cycle, improves the impregnation efficiency, and requires simple equipment, low maintenance cost, and can be mass-produced; in addition, the low-temperature pre-cracking process greatly reduces the damage to the carbon fiber matrix and improves the mechanical properties of the ceramic-based composite materials. A process combining high-temperature cracking and high-temperature ceramicization is adopted, which not only meets the requirements of impregnation and formation of ceramic reinforcement phase, but also reduces the damage of high temperature to the carbon fiber matrix to a certain extent. The PIP process is optimized by one low temperature and two high temperatures, and the prepared composite material has low porosity and uniform distribution of ceramic phase. Compared with the mechanical properties of conventional processes, the mechanical properties of the ceramic-based composite material prepared by the improved process are better, and its ablation performance has not decreased significantly, providing a more efficient process for the production of high-temperature thermal structure parts and complex parts of aerospace.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a ceramic matrix composite material by an improved PIP process, characterized in that: The steps include: 1) Pre-treat the material, select appropriate reinforcement material and matrix material, process the reinforcement material into the desired shape, and form the reinforcement material into a three-dimensional network structure through weaving, lamination or other molding processes; 2) Polymer infiltration: placing the reinforcement material in a liquid polymer, and using vacuum infiltration, pressure infiltration or room temperature infiltration, the polymer is infiltrated into the voids of the reinforcement material to fill its internal structure and form a polymer matrix; 3) Pre-cracking of the polymer matrix at low temperature: the polymer matrix after infiltration is first pre-cracking at low temperature, and the reinforcing material infiltrated with the polymer is heated; 4) High temperature cracking of the polymer matrix. To increase the density of the composite material and improve the quality of the ceramic matrix, repeated heating and cracking processes are performed to fill the original gaps; 5) High temperature ceramicization of the polymer matrix promotes the formation of ceramic reinforcement phase and makes the ceramic phase distribution more uniform.
2. The method for preparing ceramic matrix composite materials by a PIP improved process according to claim 1, characterized in that: In the step 1), the reinforcing material is carbon fiber or silicon fiber.
3. The method for preparing ceramic matrix composite materials by a PIP improved process according to claim 1, characterized in that: The liquid polymer in step 2) includes polyvinyl alcohol, epoxy resin, and phenolic resin.
4. The method for preparing ceramic matrix composite materials by a PIP improved process according to claim 1, characterized in that: In the step 3), the temperature of the low-temperature pre-cracking is 400-600° C., and the cracking time is 1-4 hours.
5. Preparation of ceramic matrix composite material by a PIP improved process according to claim 1 The method for preparing a material is characterized by: The temperature of the high temperature cracking in step 4) is 1400-1600° C., and the cracking time is 2-6 hours.
6. The method for preparing ceramic matrix composite materials by a PIP improved process according to claim 1, characterized in that: The temperature of high temperature ceramicization in step 5) is 1600-1800° C., and the cracking time is 1-2 hours.
Citation Information
Cited By
Device and method for preparing fiber-reinforced SiC ceramic-based composite material based on Joule thermochemical vapor infiltration
CN121629358A